Implementasi Akad Salam Terhadap Belanja Berbasis Live Streaming Di TikTok Shop Pada Kalangan Generasi Zoomer - Naura Dwi Arta Fitriana; Nahda Yumna Ufairoh; Abdimalik Mohamed Ibrahim Ali; Sri Wigati (JOURNAL SAINS STUDENT RESEARCH, 2025)
In the digital era, transactions can be done online, and TikTok's live feature helps sellers build trust with consumers by showcasing product quality. This study aims to analyze the implementation of the akad salam in online transactions, especially among Zoomers. Using library research, this study examines fiqh literature, articles, and scientific works, with a sociological approach based on Imam Abu Hanifah's thinking. The findings conclude that TikTok Live's sale and purchase transactions align with the akad salam. The transaction adheres to the principles of clarity, avoiding gharar, and includes an agreement on the delivery of goods, transparency about product specifications, and clear delivery times, all based on honesty and trust. TikTok, as a platform, ensures payment is forwarded to the seller only upon receipt of the goods. This indicates that TikTok can fulfill sharia principles, particularly the akad salam.